SISTEM INFORMASI GEOGRAFIS PEMETAAN POTENSI PARIWISATA TOBA SAMOSIR BERBASIS WEB - Josua Marojahan; Dedi Trisnawarman; Zyad Rusdi (Fakultas Teknologi Informasi Universitas Tarumanagara, 2018)
The purpose of making Tourism website Toba Samosir regency to provide information for the surrounding community and foreign community tho want to visit Toba Samosir regency. Website Toba Samosir Tourism can also help the Local Government of Toba Samosir regency as a media promotion of Tourism Objects in Toba Samosisr District. The method used in the making of Tourism website of Toba Samosir Regency is SDLC (System Develompent Life Cycle) constisting of several stage, namely the stages of analysis, design stages, implementation stage and maintenance stages. The result of this research is Geographic Information System of Tourism Potential Mapping of Toba Samosir Regency that is expectes to provide useful information for tourist and also help performance of Tourism and Culture Office of Toba Samosir in promoting Toursim Object of Toba Samosir Regency.